A psicodinâmica do cardiopata em emergência a partir do TAT na psicanálise bioniana - Miguel, Geyssy Yorrana Canedo (2024)
The objective of this study is to understand the psychodynamics of cardiac patients in the emergency context. Specific objectives included: understanding the patient's perception regarding their health condition and hospitalization; evoking elements of the subject's psychodynamics; investigating possible signs of a failure in the capacity to integrate sensory impressions and emotions into thinkable models; and exploring a possible predominance of primary processes and psychotic personality traits over secondary processes and non-psychotic personality traits in the subject. The methodology involved a theoretical study of Bion's work and an empirical procedure with purposive sampling, including eight patients from the cardiology ward of an emergency hospital in Goiânia. Participants were subjected to the Thematic Apperception Test (TAT), and their narratives were analyzed using Bion's conceptual framework. Two modes of functioning emerged: first, denial and refusal to engage with important and challenging themes; second, a latent expression of emotions such as sadness, loneliness, and proximity to death. The findings highlight the need to address the denial present in these patients from the onset of the illness and to implement practices aimed at reducing anxiety, providing support, and offering containment.